ESTETIKA DALAM KEHIDUPAN KEBERAGAMAAN MASYARAKAT HINDU DI BALI: SUATU PROBLEMA DEFINISI SOSIAL - I Putu Gede Parmajaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
With the religious nature of society and the universal teachings of Hinduism, almostall Hindus in Bali try to express their belief in Hyang Widhi Wasa with all its manifestationthrough the offerings of various artistry associated with worship. Art in Hindu perspective inBali has a very basic position, because it can not be separated from the Hindu communityrelegius. Aesthetic value basically refers to an autonomous discourse about the good and beautifulin the arts. In the philosophical level, art and beauty need to be explored in a way, such aspeeling from where beauty and art come from, what is the essence of the pleasure of art, and howthe process of artistic enjoyment. Artistic appreciation can not occur if the conceptualizationprocess in artists or art lovers is not perfect.